Aortic root translocation (Nikaidoh) procedure for complex transposition of the great arteries with left ventricular outflow tract obstructionCentral MessagePerspective - Emile A. Bacha, MD; Stephanie N. Nguyen, MD; Rachel Vanderlaan, MD, PhD; Damian J. LaPar, MD; Andrew B. Goldstone, MD, PhD; David M. Kalfa, MD, PhD (JTCVS Techniques)
Background: Several surgical techniques have been developed for the management of complex transposition of the great arteries with ventricular septal defect and left ventricular outflow tract obstruction (TGA/VSD/LVOTO). Aortic root translocation, or the Nikaidoh operation, offers the most anatomic biventricular repair in these patients. However, the Nikaidoh operation commonly has been limited to patients with “typical” anatomy, including a conoventricular VSD and usual coronary anatomy. We sought to describe a single surgeon’s experience with aortic root translocation for complex TGA/VSD/LVOTO. Methods: We present a series of 12 patients with complex anatomy who underwent the Nikaidoh operation over the last 13 years. Results: We report good mid- to long-term results, excellent performance of the reconstructed left ventricular outflow tract, aortic valve competence, and no coronary insufficiency. Conclusions: Our experience suggests that the Nikaidoh operation is a valid option even for patients with complex TGA/VSD/LVOTO.